Multirepresentation-Based Physics E-Module Development - Rima Buana Prahastiwi; Zahida Aliatu Zain (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
This research is a research and development with the final result of developing a multi-representation-based Physics E-Module. The development of the Physics E-Module aims to produce innovations in teaching materials that can be applied to the learning process and to support independent or student-centred learning. The Physics E-Module was developed on a multi-representational basis. Multirepresentation aims for students to get various representations of a material. The development research method used is the ADDIE design development method. This method was chosen because it is one of the basic development methods and is easy to implement. The ADDIE design development stages include Analyze, Development, Implementation, and Evaluate. The product feasibility test was carried out by involving 16 Tadris IPA Biologi UIN Mataram students. The Flip PDF Corporate supports the appearance of the multi-representation-based Physics E-Module so that the appearance of the Physics E-Module has an effect like opening a printed book. The multi-representation used in the Physics E-Module is verbal, graphic image, and audio-visual representations. Expert validators in the media and material carry out the feasibility test. The feasibility test results in the media sector are 90%, with a very feasible category. The feasibility test results in the material sector are 94.6%, with a very feasible category. The scores of the student's responses to the development of multi-representation-based Physics E-Modules range from 3.5 to 4, with a maximum score of 4. The results of this study have implications for the provision of valid and feasible Basic Physics teaching material for use in learning, especially online learning.